2020
DOI: 10.1186/s43055-020-00227-w
|View full text |Cite
|
Sign up to set email alerts
|

Is cerebral spinal fluid flow associated with body mass index and head circumference in healthy children? A phase contrast magnetic resonance imaging study

Abstract: Background: The aim of this study was to investigate the relationship between age, gender, body mass index (BMI), and head circumference (HC) and cerebral spinal fluid (CSF) flow dynamics in the pediatric population. The prospective study included a total of 137 participants, 75 boys and 62 girls, ranging in age from 2 to 204 months. Quantitative evaluation of CSF flow was made by using phase contrast magnetic resonance imaging (PC-MRI) in the axial plane at the level of the aqueductus cerebri. Flow dynamics w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Moreover, literature is also limited in relation to the evaluation of these measurements according to biometric parameters. Demirtaş et al ( 21 ) evaluated CSF flow in 137 children and found no significant correlation between body mass index and CSF flow parameters. Although we hypothesized that mean velocity and stroke volume would correlate with BSA, we found no such correlations.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, literature is also limited in relation to the evaluation of these measurements according to biometric parameters. Demirtaş et al ( 21 ) evaluated CSF flow in 137 children and found no significant correlation between body mass index and CSF flow parameters. Although we hypothesized that mean velocity and stroke volume would correlate with BSA, we found no such correlations.…”
Section: Discussionmentioning
confidence: 99%
“…Also, we did not evaluate the venous outflow abnormalities and the ventricle volumes, which is a limitation of our study. In addition, PC-MRI may result in errors in quantitative measurements, due to non-linear gradients, partial volume effects, and errors in placing ROI (Demirtaş et al, 2020).…”
Section: Zamboni Et Al (mentioning
confidence: 99%